Genome assembly and annotation of the white spot syndrome virus - infected pacific white shrimp (Ltopenaeus vannamei) in Vietnam - Tung, Nguyen Van; Lien, Nguyen Thi Kim; Thanh, Duong Chi; Hien, Nguyen Thu; Lan, Nguyen Ngoc; Ngan, Nguyen Thi Thanh; Hoang, Nguyen Huy; Trang, Trinh Thi; Ninh, Nguyen Huu; Hung, Nguyen Huu (Vietnam Journal of Biotechnology, 2021)
Pacific white shrimp (Penaeus vannamei or Litopenaeus vannamei) is native to South America, high economic value, and widely cultivated in the world and Vietnam. Over the last two decades, viral diseases have seriously threatened the shrimp aquaculture industry. Among the viral diseases, white spot syndrome virus (WSSV) is the most important viral pathogens of shrimp farming. WSSV causes a cumulative mortality can reach 100% within 3–10 days. Genome sequencing and assembly has been an important step for deciphering molecular mechanisms and accelerating genetic improvements of traits of interest in economically important species. This study aims at constructing and annotating the genome of white spot syndrome virus - infected Pacific white shrimp in Vietnam. The whole genome sequencing data was de novo assembled using SOAP denovo2 to obtained draft genome of WSSV- infected L. vannamei shrimp. The draft genome contained 3,180,049 scaffolds (genome size ~1.67 Gb) with the length arranging from 200 bp to 137,569 bp and with N50 as 616 bp. Applying gene prediction method, we have been able to identify 187,948 putative genes. The results have shown that 33,611 genes were annotate in NT database and 133,548 genes were annotated in UniProtKB/Swissprot database. These results are only the initial information about white spot syndrome virus - infected Pacific white shrimp but they are really important for future studies relating to white spot syndrome virus – resistance L. vannamei shrimp in Vietnam.